Strategi Edukasi Biro Informasi Pertahanan Kemhan RI Tentang Isu Pertahanan Melalui Podcast - Arif Mahulana Sidik; Fauzi Syarief (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
The advancement of information and communication technology has driven the utilization of social media as a strategic communication tool in various sectors, including national defense. The Ministry of Defense of the Republic of Indonesia (Kemhan RI), through the Defense Information Bureau, leverages social media platforms to educate the public on defense issues via the Podcast Pertahanan Negara (PODCAST) program. This study aims to analyze the communication approach employed by the Defense Information Bureau in PODCAST and its effectiveness in enhancing public defense literacy. This research adopts a qualitative method with a case study approach. Data collection techniques include in-depth interviews with relevant stakeholders, content observation of PODCAST episodes, and document analysis. The findings indicate that the Defense Information Bureau implements a digital communication strategy based on engagement, interactivity, and education through discussions with expert speakers and the delivery of information in an engaging manner. The program has proven effective in increasing public understanding of defense issues, yet it still faces challenges in reaching a broader audience and encouraging active public participation. The study underscores the importance of optimizing digital communication strategies in national defense education. Recommendations include enhancing two-way audience interaction, diversifying content formats, and collaborating with various stakeholders to expand the reach of defense education through social media.